2016
DOI: 10.1074/jbc.m114.629287
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor Mutations for Presenilin 1 Familial Alzheimer Disease Mutants Modulate γ-Secretase Activities

Abstract: ␥-Secretase is a multisubunit membrane protein complex containing presenilin (PS1) as a catalytic subunit. Familial Alzheimer disease (FAD) mutations within PS1 were analyzed in yeast cells artificially expressing membrane-bound substrate, amyloid precursor protein, or Notch fused to Gal4 transcriptional activator. The FAD mutations, L166P and G384A (Leu-166 to Pro and Gly-384 to Ala substitution, respectively), were loss-of-function in yeast. We identified five amino acid substitutions that suppress the FAD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…PS1 overexpression may be a risk factor for late-onset SAD (Li et al, 2011a). Conversely, inhibition of PS1 expression reduced Aβ production (Futai et al, 2016). In our study, the protein expression of PS1 showed no significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…PS1 overexpression may be a risk factor for late-onset SAD (Li et al, 2011a). Conversely, inhibition of PS1 expression reduced Aβ production (Futai et al, 2016). In our study, the protein expression of PS1 showed no significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike humans, rodents do not develop Aβ plaques in the natural aging process, which could be due to differences in the three Aβ sequences across species [ 45 ]. Several mouse models have been generated with genetic mutations related to human amyloid precursor protein (APP), C-terminal fragment of APP [ 46 ], Aβ, and familial forms of Alzheimer’s disease [ 47 - 50 ], which result in robust Aβ accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…By using these systems, it would be possible to identify proteases that modify amyloidogenesis. Moreover, a yeast system that reconstitutes β-secretase has also been established [36]. Apart from proteolysis, alternative methodology using extracellular vesicles to promote/prevent prion formation has been reported in yeast [37,38].…”
Section: Resultsmentioning
confidence: 99%